Upaya Meningkatkan Motivasi dan Prestasi Belajar Pendidikan Agama Islam pada Materi Sejarah Dakwah Islam melalui Metode Number Head Together Siswa Kelas VIII-H SMP Negeri 2 Pare - Mahmudah, Ida (Universitas Nusantara PGRI Kediri, 2023)
This study aims to describe Islamic Religious Education with the application of the Number Head Together (NHT) method which can increase student motivation and achievement in the material History of Islamic Da'wah. This study used a Classroom Action design consisting of two cycles. Based on the results of research data analysis and discussion, it can be concluded as follows: 1) The Number Head Together method can increase learning motivation in the material History of Islamic Propagation in Class VIII-H Students of SMP Negeri 2 Pare Kediri Regency Odd Semester 2022/2023 Academic Year by 20% of 71 % in cycle 1 becomes 91% in cycle 2. 2) The Number Head Together method can improve learning achievement in the material History of Islamic Da'wah for Class VIII-H Students of SMP Negeri 2 Pare Kediri Regency Odd Semester in the 2022/2023 Academic Year which is indicated by an increase in the percentage of completeness classical value of 23.67% from 63% in cycle 1 to 86.67% in cycle 2. The increase in learning achievement was also indicated by an increase in the class average value of 8.47 from 74.73 in cycle 1 to 83.2 in cycle 2.